PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH MENGGUNAKAN MEDIA INTERAKTIF UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS 5 SDN 17/I RANTAU PURI - Salsabila, Kania; Angelina, Dhella; Sari, Silfiyana; Darmawan, Hanif; Destrinelli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Based on the pre-cycle scores, it is known that of the 26 students, only 6 students met the score > KKM (70) while 20 of them had the score < KKM (70). Based on the scores in cycle 1 of the love the earth material, that of the 26 students there were only 14 students who met the score > KKM (70) while 12 of them had the score < KKM (70). If examined carefully, this score of 70 is only obtained by a small number of students in the class. So if it is a percentage, it is very far below the specified percentage of total student completion, namely 70% of the total number of students. For this reason, it is very necessary to improve the deficiencies in cycle I learning through the implementation of cycle II actions. Based on the scores in cycle 2 of the love the earth material, that of the 26 students there were only 22 students who met the score > KKM (70) while 4 of them had the score < KKM (70).